It’s essence is completely different... About Tyutchev’s formula-myth about Russianness and Russia - Broda, Marian (Myths and Stereotypes in the Collective Representations, 2019)
According to the canonical, for the Russian cultural tradition and the communal consciousness of the Russians, poetic formula presented by Fyodor Tiutchev, Russia is – unlike all the other countries, inexplicable in the notions of profane knowledge – the sacred Reality. As Wladimir Soloviev appropriately recognized the nature of the accompanying conceptualization the world, it assumes, expresses and explains the understanding of Russianhood and Russia in terms of a “soul” and the “soul of the world.” In turn, according to the identification-diagnosis by Andrzej Walicki, we are dealing here with “Tyutchev’s imperial vision,” which, please note, confirms both the content articulated by the poet in the poem On the Taking of Warsaw as well as his apoetical political texts. In the theoretical perspective, co-created by both of these interpretative methods, it is worth looking into the mythical content and implications of the analysed vision of Russianhood and Russia as well as the mental-social basis, and the consequences, of its still lasting vitality.